Relationship between emotional labor strategies and the quality of work life of operating room nurses - Li Li; Yingjuan Cao; Yingjuan Cao; Yingjuan Cao; Yinuo Sun; Yue Li; Yonghua Zhai; Yonghua Zhai; Yonghua Zhai; Yan Yan; Yan Yan; Yan Yan (Frontiers in Public Health)
IntroductionEmotional labor involves regulating one’s emotional state at work to align with organizational expectations. For operating room (OR) nurses, emotional labor is an inherent part of their roles, with different strategies potentially impacting their work-related quality of life (WRQoL) in distinct ways. This study aimed to examine the relationship between emotional labor strategies and WRQoL among OR nurses.MethodsA cross-sectional study was conducted using convenience sampling, recruiting 395 OR nurses from 11 secondary and tertiary hospitals in Shandong Province. Data were collected using the General Information Questionnaire, Emotional Labor Scale, and Work-Related Quality of Life scale. Statistical analyses, including descriptive statistics, Pearson correlation analysis, and multiple stratified regression, were applied to explore the relationships between variables.ResultsA total of 372 valid responses were obtained, with an effective response rate of 94.18%. The mean WRQoL score was 114.17 (SD = 16.54). Among emotional labor strategies, expressing naturally felt emotions was the most frequently used. Surface acting showed a significant negative correlation with WRQoL (r = −0.437, p < 0.05), while deep acting and expressing naturally felt emotions were positively correlated with WRQoL (r = 0.291 and r = 0.457, respectively, p < 0.05). Multiple stratified regression analysis confirmed that emotional labor strategies significantly influenced WRQoL.ConclusionEmotional labor strategies play a crucial role in shaping the WRQoL of OR nurses. Nursing managers should prioritize assessing nurses’ emotional labor status and provide targeted guidance to promote positive strategies, such as deep acting and expressing naturally felt emotions. Such measures can enhance nurses’ physical and mental well-being, ultimately improving their quality of work life.